Firm value model from the perspective of firm profitability and dividend-paying behavior with dividend payout as a mediator - Iskandar Iskandar; Syamsurijal Tan; Tona Aurora Lubis; Asep Machpudin (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2022)
This study aims to analyze and explain the firm value model from the perspective of a firm’s profitability and dividend-paying behavior with dividend payout as a mediator. The population used is the stock in the LQ45 Index for the 2017-2019 period. The sample was determined using the judgment sampling type purposive sampling method to obtain 26 companies. The analytical method used is Partial Least Square (PLS). The study results show that a firm’s profitability can increase dividend payout, but firm’s profitability is not able to increase the firm’s value. Dividend-paying behavior does not affect dividend payout, but the behavior of paying dividends can increase the company's value. Dividend payout can increase the value of the company. On the other hand, dividend payout cannot mediate firm’s profitability to firm value, but on the contrary, dividend payout can mediate the behavior of dividend payout to firm value.